Causes of transformer failures and diagnostic methods – A review. (February 2018) - AJ, Christina; Salam, M.A.; Rahman, Q.M.; Wen, Fushuan; Ang, S.P.; Voon, William
Abstract: This paper presents a review on the sources of failures of transformer in the substation. Different investigations and test analyses have been conducted to identify the root causes of failure of the transformer in the power system, and to identify the preventive measures to avoid these breakdowns. The review work has been presented with the focus on bushing-failure, which has been identified as one of the major causes of transformer breakdown in different reported studies. In determining the lifespan of the insulation of the high voltage bushing, along with different factors, moisture effect has also been considered in presenting the degradation analysis. On-line measurement has been preferred over off-line measurements due to its benefits measuring the reliability and uninterrupted functioning of the future generation, transmission and distribution systems. Post fire-outbreak, external inspection of the damaged bushing along with analytical results, obtained with the aid of Scanning Electron Microscope (SEM) and Energy Dispersive X-ray Spectroscopy (EDS) analysis, have also been included in this study. In the analysis, electric field and equipotential lines with different oil levels have been simulated using COMSOL Multiphysics software.